Paraguay : 2016 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses the recent economic developments of Paraguay. Against the backdrop of a regional slowdown, Paraguay's economy remains relatively resilient. The economy experienced some loss of momentum over the past year due to unfavorable external shocks. Inflation pressures remain contained despite significant depreciation of the guarani against the U.S. dollar. Macroeconomic policies remain accommodative in light of subdued inflation and slower growth. Recently, credit growth has moderated, but credit quality has deteriorated. To further strengthen fiscal, monetary, and financial sector policy frameworks, Paraguay outlines structural reform agenda and measures. The national development plan places emphasis on inclusive growth and poverty reduction.